2016
DOI: 10.1007/s11698-016-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

Transatlantic wage gaps and the migration decision: Europe–Canada in the 1920s

Abstract: As has been seen in other contexts, workers in similar occupations earned much higher wages in Canada than Europe during the 1920s. This observation and related aspects of immigration are addressed with a life-cycle model of the migration decision. The characteristics of immigrants from five European countries: Ireland, Italy, the Netherlands, Poland, and Sweden, are explored in a way that sheds light not just on those population flows but on the process of immigration generally. We draw on passenger manifests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the Hesse Cassel region of Germany from 1832 to 1857 Wegge (1998) found that networked emigrants carried less cash with them. By the 1920s these effects were weaker but Armstrong and Lewis (2017) provide evidence that the need to save served to delay emigration to Canada.…”
Section: Determinants Of International Migrationmentioning
confidence: 99%
“…In the Hesse Cassel region of Germany from 1832 to 1857 Wegge (1998) found that networked emigrants carried less cash with them. By the 1920s these effects were weaker but Armstrong and Lewis (2017) provide evidence that the need to save served to delay emigration to Canada.…”
Section: Determinants Of International Migrationmentioning
confidence: 99%
“…The 1920s is also the focus of Alex Armstrong and Frank Lewis's () work on migration. They use ship passenger manifests to help explain the large wage differences between Canada and the countries of origin of the immigrants.…”
Section: Migrationmentioning
confidence: 99%